Age calibration of the Lower Ordovician Fezouata Lagerstätte, Morocco. (19th September 2017) - Lefebvre, Bertrand; Gutiérrez‐Marco, Juan C.; Lehnert, Oliver; Martin, Emmanuel L. O.; Nowak, Hendrik; Akodad, Mustapha; El Hariri, Khadija; Servais, Thomas
Abstract : The Fezouata Lagerstätte, discovered in the Lower Ordovician rocks of Morocco, is a Konservat‐Lagerstätte of prime scientific importance. It provides access not only to the 'shelly' (skeletonized) part of its fossil assemblages, but also to non‐biomineralized to lightly sclerotized organisms and to exceptionally preserved soft tissues of a complex ecosystem, mixing elements of both the 'Cambrian Explosion' and the 'Great Ordovician Biodiversification Event' (GOBE). The Fezouata Lagerstätte occurs at different intervals in the Fezouata Shale, a formation ranging from the lower Tremadocian to the upper Floian (Lower Ordovician). In spite of recent major advances in the detailed biostratigraphy of the Fezouata Shale, there is currently no consensus on the precise age of the fossiliferous levels yielding exceptionally preserved assemblages. Consequently, all available biostratigraphical evidence based on several fossil groups is here critically reviewed and discussed. It can be concluded that exceptional preservation is restricted to a few thin, discontinuous, lens‐shaped horizons occurring in two distinct parts of the Fezouata Shale: a lower interval (260–330 m above the base of the formation) and an upper interval (570–620 m). Integrated biostratigraphical studies, essentially based on investigations of graptolites, acritarchs and conodonts, indicate that the lower interval can be correlated with the upper Tremadocian, whereas the upper interval corresponds to the middle Floian.